Farmers’ Perceptions and Behavior which Affecting the Adoption Rate of KUB Chickens - Iif Syarifah; Sitti Nurani Sirajuddin; Syahdar Baba; Mukhamad Najib (Jurnal Ilmu Ternak dan Veteriner, 2023)
KUB chicken as a superior breed produced by Indonesian Agency for Agricultural Instrument Standardization (IAAIS) becomes one of the solutions in an effort to increase the need for animal protein. KUB chicken breeds have been successfully disseminated to all provinces in Indonesia. Thus the rate of adoption and behavior of breeders in maintaining the sustainability of KUB chicken rearing needs to be analyzed  because the breeds that are disseminated may not be successfully developed in a certain area. This research will collaborate between the two theories; "Theory of Planned Behavior" (TPB) and "Technology Acceptance Model" (TAM). It was conducted in June 2022 in the City of Salatiga, Semarang and Magelang, Central Java Province. The determination of the research location was based on the consideration that there was a KUB chicken breeders group that already had a KUB chicken breeder association called AnaKUB (KUB Chicken Breeders Association) and a breeding population that met the sampling requirements. The purpose of this research was to analyze the perception factors and breeders behavior that affect the adoption rate of KUB Chicken Technology in Central Java Province, Indonesia. ). The combined results of path analysis (path) and regression analysis on the Structural Equation Modeling (SEM) technique, it can be concluded that perceived benefits (25.3%), ease of raising KUB chickens (23.9%), attitudes (21.2%), subjective norms (16.7%) and perceptions of control behavior (17.3%) have a positive effect on the intention to adopt KUB chickens. The perceived benefits (45.8%) and the perceived ease of raising KUB chickens (50.1%) have a very positive effect on the attitude variable of the farmer. Important people including family members have an important role in supporting the maintenance of KUB chickens, while extension workers have not contributed much in supporting breeders to adopt KUB chickens. Collaboration of two theories has a mutually influencing relationship, especially towards attitudes and intentions to adopt KUB chickens which have a positive effect on the adoption rate. The adoption rate of KUB chicken is 3.32 (66.40%), this shows that the adoption rate of breeders in the Central Java region, is classified as high adoption.